2023
DOI: 10.1002/smll.202300534
|View full text |Cite
|
Sign up to set email alerts
|

Rational Engineering of p‐n Heterogeneous ZnS/SnO2 Quantum Dots with Fast Ion Kinetics for Superior Li/Na‐Ion Battery

Abstract: Constructing heterogeneous nanostructures is an efficient strategy to improve the electrical and ionic conductivity of metal chalcogenide‐based anodes. Herein, ZnS/SnO2 quantum dots (QDs) as p‐n heterojunctions that are uniformly anchored to reduced graphene oxides (ZnS‐SnO2@rGO) are designed and engineered. Combining the merits of fast electron transport via the internal electric field and a greatly shortened Li/Na ion diffusion pathway in the ZnS/SnO2 QDs (3–5 nm), along with the excellent electrical conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…This is because as the cycle proceeds, the active substances are gradually activated, which is expressed as a rise in capacity. 43 This also holds true for SC and SnO 2 , as shown by long cycling of SC at 1.0 A g −1 (Figure S1), where the capacity is realized as a decrease followed by an increase. The initial part of the capacity loss is due to the generation of an irreversible SEI film and Li 2 O.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…This is because as the cycle proceeds, the active substances are gradually activated, which is expressed as a rise in capacity. 43 This also holds true for SC and SnO 2 , as shown by long cycling of SC at 1.0 A g −1 (Figure S1), where the capacity is realized as a decrease followed by an increase. The initial part of the capacity loss is due to the generation of an irreversible SEI film and Li 2 O.…”
Section: Resultssupporting
confidence: 63%
“…It can be observed that the discharge capacity of SNC has a slow decreasing trend in the initial stage until after 100 cycles, the capacity slowly increases and finally reaches a large reversible discharge capacity of 1245.7 mA h g –1 when it is cycled to 400 cycles. This is because as the cycle proceeds, the active substances are gradually activated, which is expressed as a rise in capacity . This also holds true for SC and SnO 2 , as shown by long cycling of SC at 1.0 A g –1 (Figure S1), where the capacity is realized as a decrease followed by an increase.…”
Section: Results and Discussionmentioning
confidence: 57%
“…3c). 6 The two characteristic peaks centred at about 495.6 and 487.3 eV in the Sn 3d XPS spectra are assigned to Sn 3d 3/2 and Sn 3d 5/2 of Sn 4+ species, 27 respectively (Fig. 3d).…”
Section: Resultsmentioning
confidence: 97%
“…3 Metal oxides (SnO 2 , Fe 3 O 4 , ZnO, MnO, etc. 4–7 ) and metal sulfides (Sb 2 S 3 , MoS 2 , ZnS, FeS, etc. 8–12 ) as conversion reaction-based electrodes stand out from various LIB anode materials due to their low cost and high theoretical specific capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation